Stagnation-point flow of a hybrid nanoliquid over a non-isothermal stretching/shrinking sheet with characteristics of inertial and microstructure - Khan, Umair; Zaib, Aurang; Abu Bakar, Sakhinah; Ishak, Anuar (Case studies in thermal engineering, 2021)
Nanoliquid is a modern invention that is very promising in improving the heat transfer capabilities. The most critical disadvantage of classical nanoliquid models is that they cannot express categories of liquids that have definite microscopic characteristics that occur from the local structure and micro-rotation of the fluid elements. In this article, the features of the micro-rotation and heat transfer characteristics of a micropolar hybrid nanofluid flow towards a stagnation point on a stretching/shrinking sheet are analyzed numerically. The similarity transformation is utilized to transform the governing equations to a set of nonlinear ordinary differential equations before they are solved numerically using the function bvp4c in MATLAB software. The dual nature of solutions of shear stress, heat transfer, and micro-rotation gradient are illustrated for a broad range of pertaining parameters. The separation of boundary-layer takes place when multiple results fail to happen beyond a critical value of the shrinking parameter. The outcomes show that the separation of boundary layer is delayed due to mass suction parameter while the contrary behavior is observed for the effects of the volume fraction of nanoparticles. In addition, the friction factor initially uplifts and then declines due to suction for the first solution, while decelerates for the second solution but the heat transport and micro-rotation gradient enhance due to suction for both solutions. The temperature augments for both solution branches due to nanoparticles volume fraction while the micro-rotation and the velocity shrink for the first solution branch while uplift for the lower solution branch.